2020
DOI: 10.1007/s10995-019-02854-w
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Programs to Promote Aspects of Teen Parents’ Self-sufficiency: Supporting Educational Outcomes and Healthy Birth Spacing

Abstract: Introduction Expectant and parenting teens experience many challenges to achieving self-sufficiency and promoting their children's healthy development. Teen parents need support to help them address these challenges, and many different types of programs aim to support them. In this systematic review, we examine the research about programs that aim to support aspects of teen parents' self-sufficiency by promoting their educational outcomes and healthy birth spacing. Methods We conducted a comprehensive literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 74 publications
(121 reference statements)
2
13
0
Order By: Relevance
“…These results are supported by findings from a well-conducted randomized controlled trial of Healthy Families Healthy Futures enhanced with Steps to Success, a home visiting program for teen parents, which found suggestive evidence of increases in use of long-acting reversible contraceptives among the treatment group (Zief et al 2020b , this issue). Finally, consistent with other research (Corcoran and Pillai 2007 ), the systematic review found programs reduced repeat pregnancies or births, particularly rapid repeat pregnancies or births that occurred within 24 months of prior births (Harding et al 2020 , this issue). Overall, the supplement provides rigorous research about programs that promote teen parents’ education, increase contraceptive use, or reduce repeat pregnancies.…”
Section: Programs Can Improve Outcomes For Teen Parentssupporting
confidence: 84%
See 3 more Smart Citations
“…These results are supported by findings from a well-conducted randomized controlled trial of Healthy Families Healthy Futures enhanced with Steps to Success, a home visiting program for teen parents, which found suggestive evidence of increases in use of long-acting reversible contraceptives among the treatment group (Zief et al 2020b , this issue). Finally, consistent with other research (Corcoran and Pillai 2007 ), the systematic review found programs reduced repeat pregnancies or births, particularly rapid repeat pregnancies or births that occurred within 24 months of prior births (Harding et al 2020 , this issue). Overall, the supplement provides rigorous research about programs that promote teen parents’ education, increase contraceptive use, or reduce repeat pregnancies.…”
Section: Programs Can Improve Outcomes For Teen Parentssupporting
confidence: 84%
“…The evidence in this supplement demonstrates that programs can improve aspects of teen parents’ self-sufficiency. Specifically, a systematic review found 14 programs with rigorous evidence of improving teen parents’ education, increasing contraceptive use, or reducing repeat pregnancies (Harding et al 2020 , this issue). Consistent with prior work (Steinka-Fry et al 2013 ), this systematic review found that programs can improve teens’ educational outcomes, particularly outcomes related to educational progress such as school enrollment (Harding et al 2020 , this issue).…”
Section: Programs Can Improve Outcomes For Teen Parentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Programs designed to address the needs of young expectant or parenting mothers often use multiple components and approaches, involving numerous partners (Person et al 2018 ). The body of evidence on the effectiveness of some of these programs is growing, but there is still a lack of knowledge about the different components and attributes that coalesce to drive program success (Harding et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%